2010
DOI: 10.1371/journal.pone.0013603
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Epstein Barr Virus Latency Pattern in Argentine Breast Carcinoma

Abstract: IntroductionEpstein-Barr virus (EBV)-associated tumors show different expression patterns of latency genes. Since in breast carcinoma this pattern is not yet fully described, our aim was to characterize EBV latency pattern in our EBV positive breast carcinoma series.MethodsThe study was conducted on 71 biopsies of breast carcinoma and in 48 non-neoplastic breast controls. EBNA1, LMP2A and LMP1 expression was assessed by immunohistochemistry with monoclonal antibodies, while viral genomic DNA and EBERs RNA tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 35 publications
6
47
0
1
Order By: Relevance
“…2016; 11(3):e34806. (11,18,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Table 1 shows a summary of the EBV-DNA positive subjects according to nationality, types of sample, and kinds of control tissue in the 20 selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…2016; 11(3):e34806. (11,18,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Table 1 shows a summary of the EBV-DNA positive subjects according to nationality, types of sample, and kinds of control tissue in the 20 selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…3 Several other recent studies, including 3 from the Middle East, showed clearly that EBV is present in 30-50% of human breast cancer. [4][5][6][7][8] Overall, these studies demonstrate that EBV is present in human breast cancer; given the biological actions of EBV-derived onco-proteins, it is quite possible that it plays an important role in the initiation and/or progression of this malignancy. This is based on our study as well as recent investigations about the role of LMP1 and EBNA1 onco-proteins of EBV in the initiation of epithelialmesenchymal transition (EMT) in human nasopharyngeal cancer.…”
mentioning
confidence: 77%
“…The expression patterns of the different latent genes define these latency programs (80). The latency protein EBV-encoded nuclear antigen 1 (EBNA1) is vital for the replication of the viral genome and therefore is expressed in all types of latencies.…”
Section: Epstein-barr Virusmentioning
confidence: 99%